Differentiating Characteristics of Intimate Partner Violence: Do Relationship Status, State, and Duration Matter? - Sutton, Danielle (Journal of interpersonal violence, 2021)
A growing body of literature has been devoted to analyzing the relationship status and state between victim and perpetrator to understand the dynamics of intimate partner violence (IPV). Prior research revealed that IPV was more frequent and severe in cohabiting and estranged relationships relative to marital/dating and intact relationships, respectively. Violence in cohabiting unions, however, has declined in recent years potentially due to the increasing popularity of such unions and their growing similarity to legal marriages. The use of relationship duration as a focal variable in analyzing the characteristics of IPV incidents, however, has received inadequate attention within the field. This study addresses this gap and builds upon existing research by exploring whether characteristics of IPV differ depending on the status, state, and duration of relationship by examining IPV cases documented in Crown Attorney files in one Ontario jurisdiction between 2003 and 2009. Through bivariate and multivariate analyses, current findings reveal that IPV involving marital, compared with dating, unions is more severe because of weapon use. Contradictory to previous research, IPV occurring among estranged intimate partners, compared with those in intact unions, is less likely to involve physical injury or weapon use. Finally, situational, in comparison with demographic, characteristics are affected less by the relationship duration between the perpetrator and victim. Several explanations for these findings are discussed along with study limitations and practical implications in terms of preventive measures, and it concludes with areas for future research.